The Role of Technology in Promoting Diversity and Inclusion - William J. Triplett (Cybersecurity and Innovative Technology Journal, 2023)
Diversity and inclusion are vital organization priorities, as they connect clearly to organizations. Digital technology has revealed that it can connect individuals into successful teams with substantial benefits in promoting diversity and inclusion. This observation establishes the need to make sure complete entry to digital technology, regardless of economic, social, and cultural background. There was a significant positive impact when technology was used to promote diversity and inclusion. The findings of our rigorous investigation suggest that technology plays a vital role in promoting diversity and inclusion.